Analiza dokładności wyników symulacji stochastycznej na przykładzie równania regresji - Jankowska, Ilona (Accuracy Analysis of Stochastic Simulation's Results Applied in Linear Regression, 2007)
The paper describes an exemplary application of stochastic simulation to analysis of results' accuracy. Reliability and certainty of the solution is the subject of the discussion. The main purpose of the investigation is to determine the desirable number of replications using experimental simulations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 93-102